PREZI, CLOUD-BASED PRESENTATION, FOR TEACHING: HOW IS IT INTERESTING? - Santiana Santiana; Asri Siti Fatimah (EduLite: Journal of English Education, Literature and Culture, 2017)
This study aims at analyzing reflection of the use of prezi as instructional media for teaching English in Indonesian context. Prezi is presentation software which is not commonly used in Indonesia producing a cloud-based presentation and storytelling tool for presenting ideas on a virtual canvas. This study is conducted based on the previous survey study done by Fox et.al (2016) finding that all of the students in their study preferred prezi rather than power point as a presentation tool in the areas of ease of use, fun to use, text, graphics, and usage in future presentations. However, this study has a purpose to reflect the student-teacher’s experience when using prezi in teaching English. To obtain the data, journal writing and self-observation by using video recording are used. It deeply investigates: 1) how he creates prezi for teaching English and 2) challenges and benefits of using it for teaching. The finding revealed that prezi is a powerful tool attracting the students’ attention which creates better classroom atmosphere and meaningful learning experience. On the other hand, it encourages the teacher to have high access of internet and be creative on making prezi presentation.